Alley cropping with Sesbania - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
In order to reduce the destruction of indigenous forest, ways have to be devised to grow more crops on the same land without resorting to expensive fertilizers or technology. One such way is alley cropping; planting leguminous trees in between...